FACTORS THAT AFFECT INEQUALITY DISTRIBUTION INCOME IN CENTRAL JAVA - Soeharjoto Soeharjoto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Sustainable development can increase economic growth and income distribution more equitable. This become a challenge for the Central Java province with a large area of population in overcoming income distribution inequality. Aims of this study is to determine factors that influence income distribution inequality in Central Java. Panel data regression method with fixed effect models are used. Inequality income distribution as a dependent variable and the independent variables are GRDP, agglomeration of industrial sector, agglomeration of trade, agglomeration of agriculture, inflation, level of labor force participation, and domestic investment. Results show that industrial agglomeration has a positive and significant effect on inequality income between districts and cities in Central Java. GRDP, agricultural agglomeration and level of labor force participation have a negative and significant effect on inequality income between districts and cities in Central Java. The influence of the trade agglomeration, inflation, and domestic investment is not significant to inequality income between districts and cities in Central Java.